2012
DOI: 10.1111/j.1445-5994.2011.02647.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers faced by migrants in accessing healthcare for viral hepatitis infection

Abstract: Substantial hurdles identified by participants include cultural differences, language difficulties, cultural beliefs, stigma and misinformation. These data demonstrate the need for the greater dissemination of information in culturally and linguistically appropriate mediums to raise awareness about viral hepatitis, pathogenesis and available treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 21 publications
4
48
0
Order By: Relevance
“…This was demonstrated in an Australian study, where lack of knowledge about antiviral treatment was identified as a major obstacle to accessing healthcare among migrants. 19 Misunderstanding about the transmission of hepatitis B through sharing food and utensils was identified among participants and reflects the findings of other studies. [16][17][18] In a health professionals are a trusted source of information for people with CHB.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This was demonstrated in an Australian study, where lack of knowledge about antiviral treatment was identified as a major obstacle to accessing healthcare among migrants. 19 Misunderstanding about the transmission of hepatitis B through sharing food and utensils was identified among participants and reflects the findings of other studies. [16][17][18] In a health professionals are a trusted source of information for people with CHB.…”
Section: Discussionmentioning
confidence: 82%
“…[16][17][18] In a health professionals are a trusted source of information for people with CHB. 16,19 Educating people with CHB was identified by Australian GPs as an important responsibility in their clinical management 20 although systemic barriers have been identified in providing this support, given GPs' busy schedules and workloads, 21,22 and hepatitis B knowledge gaps among some GPs. 21,23 A study from one tertiary hospital liver clinic reported that clinicians did not provide detailed information about hepatitis B during most ongoing monitoring consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese people in China and in the USA were the most studied groups. [242526272829303132333435] The participants were HBV-infected patients, members of the general community, health-care providers, or community leaders [Tables 1 and 2]. All participants were adults.…”
Section: Resultsmentioning
confidence: 99%
“…Access to high-quality health care remains a fundamental problem for international migrants. They encounter a number of barriers, which include language difficulties [4–6], cultural differences [4, 7], economic barriers [5, 7], legal problems [8, 9], and social isolation [5, 6]. A majority of the migrant health research has been focused in Western settings; little is known about how international migrants access health services in Asian countries [10].…”
Section: Introductionmentioning
confidence: 99%